Evidence for Stuttering Disfluencies to be Both the Result of Impaired Speech Production System and Coping Response to the Impairment - Horabail S. Venkatagiri; NP, Nataraja (Journal of All India Institute of Speech and Hearing)
The present study analyzed the topography of recurrent stutters (stutters on same words in repeated readings) in a group of 22 adolescents and adults who stutter to explore whether stutters are the direct result of impaired speech production system or coping responses to an underlying impairment. If stutters are the direct result of an impairment, there should be more concordant re-currences (stutter of a certain type on a word in one reading is followed by stutter of the same type if the word is stuttered in the next reading of the passage) than discordant recurrences. Signi cantly greater number of discordant recurrences suggests that stutters may be coping responses to an underlying impairment. The present study found signi cantly more concor- dant than discordant recurrences indicating at least some stutters are the direct result of impaired speech production system. Results of the study also suggest that non-repetitive stutters (dysrhythmic phonations) may be coping responses.